Multidimensi Pengemas Obat : Inovasi, Informasi, dan Perlindungan Konsumen - Mahabatul Hasanah; Siti Fatimatuzzahra; Nor Latifah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Drug packaging not only serves as a protective barrier for pharmaceutical products but also functions as a strategic element in conveying information and ensuring consumer rights. This study is a literature review of five journals that discuss packaging innovation, legal aspects of labeling, consumer protection, and packaging design from both technological and regulatory perspectives. The aim of this study is to compare the dimensions of innovation, information, and protection in drug packaging. A narrative review method with a qualitative descriptive approach was used. The results show that innovations such as the use of adsorbent plastic and efficiency in packaging systems significantly affect product stability and production speed. Meanwhile, the inclusion of composition details and halal labeling on packaging serves as a form of consumer protection from health risks and rights violations. It is concluded that a multidimensional approach to drug packaging is essential in creating a pharmaceutical distribution system that is efficient, safe, and ethical.